Desire for development: seeking social change though climate adaption projects. Issue 2 (17th February 2020) - Rubinov, Igor
ABSTRACT: This article considers why residents of Tajikistan seek out development projects, which are increasingly focused on adaptation to climate change, even as they recognise the limitations of those projects. Experiences of meaningful development during the Soviet era, along with foreign media accounts and migrant experiences abroad, reoriented people's expectations and encouraged them to seek aid. As a result, people sought out personal networks to guide development projects in the hopes of bolstering their ongoing livelihood strategies. Efforts to promote participation in development must account for the desires people hold in order to guide how projects are devised and implemented.